Immigration and the Diffusion of Technology: The Huguenot Diaspora in Prussia - Erik Hornung (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
This paper analyzes long-term effects of skilled-worker immigration on productivityfor the Huguenots migration to Prussia. We combine Huguenot immigration lists from1700 with Prussian firm-level data on the value of inputs and outputs in 1802 in aunique data base. In 1685, religious persecution drove highly skilled Huguenots out ofFrance into backward Brandenburg-Prussia where they were channeled into towns tocompensate population losses due to plagues during the Thirty Years War. Exploitingthis settlement pattern in an instrumental-variable approach, we still find causal effectsof Huguenot settlement on the productivity of textile manufactories hundred years aftertheir immigration.
Keywords: N33; J24; O33; F22; 330; Migration; technological diffusion; human capital; Huguenots; Prussian economic history; Einwanderung; Protestantismus; Siedlung; Textilindustrie; Produktivität; Technologietransfer; Schätzung; Preußen